Optimalisasi Penghawaan Alami melalui Tata Ruang di Rumah Susun Bertingkat Rendah - Fuad Rizal (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2018)
ABSTRACTÂ Quality of natural ventilation in low rise public housing in Jakarta tends to be low. Situation mentioned above presumably caused by several case, among other form and unadequate opening placement, unadequate furniture placement, form and orientation of public housing mass and minimum building protection from sun radiation. Whereas natural ventilation have an importent role in increasing indoor air quality, increasing occupant healthy and help increasing electricity consumption eficiency. The objective of this research is attempt solving natural ventilation problems in low rise public housing architecturally through designs that could used for occupant activity precisely and presenting good natural ventilation simultaneously so it can support occupant activity in public housing as efficiently, comfortable, healthy and secure. Research begins with conduct an observation towards existing public housing in Jakarta through interview, documentation of existing public housing condition and studying public housing designs through working documents and related standards. Collecting climate data especially wind velocity conducted to get illustration of condition that take place in definite period. Those data then analyzed to produce a model formula of public housing building that tested later with computer. The result of research show that the problems of natural ventilation in low rise public housing can be solved by accurately building design that can adapt with surrounding nature. Quite significant positive change occurs after modification does to the existing unit. Hopefully government through certain official can produce public housing design which more optimal, especially in natural ventilation. People also could knowing the caused of natural ventilation problems inside the room also could solving it by simply, efficiently and accurately through the result of this research. Some advantages occupant could gained are good and prevalent airflow inside the room, reducing air conditioning equipment utilization frequency, less maintenance cost and can it can works all the time. Â Keywords: natural ventilation, sun radiation, electricity consumption efficiency, indoor air quality, low rise public housing, wind velocity